Analisis Kekeringan Meteorologis dan Hidrologis DAS Brantas, Kabupaten Trenggalek - Alan Wijaya; Asep Ferdiansyah (Direktorat Bina Teknik Sumber Daya Air, Kementerian Pekerjaan Umum dan Perumahan Rakyat, 2026)
Trenggalek Regency in East Java Province is considered vulner between these two drought typesable to drought due to uneven rainfall distribution and predominantly hilly topography. This study aims to assess the levels of meteorological and hydrological drought hazards and to examine the relationship between these two types of drought within the region. Meteorological drought was analyzed using the three-month Standardized Precipitation Index SPI-3, derived from rainfall records obtained from 18 rainfall stations. Hydrological drought was evaluated using the three-month Standardized Runoff Index SRI-3, based on discharge data from several streamflow gauging stations within the Brantas sub-watersheds. The spatial distribution of drought hazards was mapped using the Inverse Distance Weighted (IDW) interpolation method within a spatial analysis framework. The results indicate that the southern coastal area of Trenggalek Regency experiences high to very high meteorological drought hazard, whereas the mountainous regions exhibit relatively lower drought hazard due to higher rainfall intensity. Hydrological drought analysis reveals that drought hazard levels vary from very low to moderate across several gauging stations. The discrepancy between meteorological and hydrological drought conditions is influenced by the presence of baseflow derived from groundwater storage, which helps sustain river discharge during dry periods. Correlation analysis between SPI-3 and SRI-3 demonstrates a positive relationship, with correlation coefficients ranging from 0.41 to 0.79, indicating that meteorological drought generally precedes hydrological drought with a detectable lag time. These findings provide important insights for improving drought mitigation strategies and supporting sustainable water resources management in Trenggalek Regency